Exact solution of the multi-trip inventory routing problem using a pseudo-polynomial model - Braga, Nuno (2017)
In this paper, we address an inventory routing problem where a vehicle can perform more than one trip in a working day. This problem was denominated multi-trip vehicle routing problem. In this problem a set of customers with demand for the planning horizon must be satisfied by a supplier. The supplier, with a set of vehicles, delivers the demand using pre-calculated valid routes that define the schedule of the delivery of goods on the planning horizon. The problem is solved with a pseudo-polynomial network flow model that is solved exactly in a set of instances adapted from the literature. An extensive set of computational experiments on these instances were conducted varying a set of parameters of the model. The results obtained with this model show that it is possible to solve instances up to 50 customers and with 15 periods in a reasonable computational time.